2021
DOI: 10.1126/science.abg2371
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen reduction to ammonia at high efficiency and rates based on a phosphonium proton shuttle

Abstract: Ammonia (NH3) is a globally important commodity for fertilizer production, but its synthesis by the Haber-Bosch process causes substantial emissions of carbon dioxide. Alternative, zero-carbon emission NH3 synthesis methods being explored include the promising electrochemical lithium-mediated nitrogen reduction reaction, which has nonetheless required sacrificial sources of protons. In this study, a phosphonium salt is introduced as a proton shuttle to help resolve this limitation. The salt also provides addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
338
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(384 citation statements)
references
References 45 publications
2
338
0
Order By: Relevance
“…The developed design principles in the form of above-threshold constraints on Kamlet–Taft α and β parameters provide a rationale not only for the promising candidates identified in this study but also others reported in the literature. For example, a concurrent work by Suryanto et al 48 reports a phosphonium-based proton shuttle with high Faradaic efficiency for a very similar scheme, the performance of which can be rationalized based on our design rule given that the phosphonium cation exhibits high KT parameter values as reported from other literature. 49 , 50 In light of this independent corroboration, we identify ionic liquids that exhibit high KT parameter values to be promising candidates for exploration in a subsequent effort.…”
Section: Discussionmentioning
confidence: 61%
“…The developed design principles in the form of above-threshold constraints on Kamlet–Taft α and β parameters provide a rationale not only for the promising candidates identified in this study but also others reported in the literature. For example, a concurrent work by Suryanto et al 48 reports a phosphonium-based proton shuttle with high Faradaic efficiency for a very similar scheme, the performance of which can be rationalized based on our design rule given that the phosphonium cation exhibits high KT parameter values as reported from other literature. 49 , 50 In light of this independent corroboration, we identify ionic liquids that exhibit high KT parameter values to be promising candidates for exploration in a subsequent effort.…”
Section: Discussionmentioning
confidence: 61%
“…Future investigations should consider additional process arrangements for their ability to drive down the process energy demand. For example, increasing the faradaic efficiency of the process is key to achieving low energy demand due to the flow on effect observed here for the balance of plant energy demands and is likely to outweigh energy trade-offs such as high cell voltage as seen in recent breakthroughs in the electrochemical ammonia field (Suryanto et al, 2021). Understanding all process requirements for direct electrochemical ammonia can help direct research efforts and work outlined here should be expanded on for other electrochemical systems such as aprotic and redox mediated approaches.…”
Section: Optimised Performancementioning
confidence: 98%
“…Some evidence that increasing the temperature up to 60 °C can improve both faradaic efficiency and yield considerably has been presented (Qin et al, 2018) and therefore as a conservative estimate 60 °C has been used for both hydrogen and water fed cells since this is also the operational temperature of electrolysis and fuel cells and reduces process complexity. The majority of authors have not attempted to pressurise the cell, although Suryanto et al (2021) recently presented an interesting study with increased pressure on the cathode side showing high performance. Ambient pressure is assumed here however in keeping with most approaches for electrochemical ammonia formation.…”
Section: Electrochemical Ammonia Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Recently, Suryanto et al have reported even more promising results on electrochemical synthesis of NH 3 in a phosphonium salt in place of ethanol and achieved a high NH 3 production rate of roughly 53 × 10 À 9 mol cm À 2 s À 1 and a faradaic efficiency of around 69 % for 20 h under 0.05 MPa H 2 and 1.95 MPa N 2 . [20] Chemical methods for the nitrogen fixation with Li and the NH 3 synthesis have also been explored extensively. For example, McEnaney et al proposed a LiÀ Li 3 NÀ LiOH loop for NH 3 synthesis.…”
Section: Introductionmentioning
confidence: 99%